Effects of Cooking on Anthocyanin Concentration and Bioactive Antioxidant Capacity in Glutinous and Non-Glutinous Purple Rice - Supaporn Yamuangmorn (2018)
© 2018 China National Rice Research Institute Purple rice is a source of bioactive antioxidants for rice consumers. Loss of the major antioxidant compounds after a range of cooking processes was evaluated by measuring the changes in anthocyanin concentration (ATC) and antioxidant capacity (DPPH activity) of four non-glutinous and four glutinous genotypes. However, soaking in water prior to cooking generally decreased more ATC and antioxidant capacity in non-glutinous than in glutinous genotypes. Wet cooking (WC) and soaking before wet cooking (S-WC) led to lose almost all the ATC and antioxidant capacity with only slight variation between genotypes. In the glutinous genotype Pieisu, which had the highest raw rice ATC, ATC remained the highest when cooked by the WC method. By contrast, almost no ATC remained after WC and S-WC in the low ATC genotypes such as Kum Doi Saket. Overall, the loss of ATC was greater in non-glutinous than in glutinous genotypes for both WC and S-WC methods, but the reverse occurred for antioxidant capacity. WC using electric rice cooker retained higher ATC than the pressure cooking. Thus, for genotypes with high ATC and antioxidant capacity, the selection of cooking method is critical for retaining and stabilizing rice quality.